As instituições museológicas e as práticas de lazer: uma revisão bibliográfica do período entre 2011 e 2015 - Evaldo Pereira Portela (2015)
Currently, the museums are gaining new status and has grown in the leisure industry. There is an increase of various types of museums in the world, which puts the public at the center of your attention. Consider the visitor in their marketings and in their planning, facilitating the physical access and intellectual to public. It has been hypothesized that the leisure industry has expanded and transformed the relationship of the public with the museums and able to print this space as a venue for leisure practices and tourist attraction. This research aims to investigate scientific literature the relationship between museums and leisure practices nowadays. To achieve this goal, it used the search for bibliographic review in four online databases, them being: SCIELO (Scientific Electronic Library Online), LILACS (Latin American and Caribbean Literature in Health Sciences), SCOPUS (production of research in the world in the areas of science, technology, medicine, social sciences, arts and humanities) and WEB OF SCIENCE (is a set of databases with indexing in sciences, social sciences, arts and humanities). Had as descriptors in English: Museum and Leisure associated. From the inclusion and exclusion criteria were selected the analyzed articles. The included, complete articles of research and experiment reports published in journals available in the databases mentioned above in the period between the years 2011 and 2015. Was analyzed the relationship between museums and practices of leisure and constituted in three categories: new museology, leisure in museums and marketing in museums. Notes that there are few studies in the international framework that treat the binomial museum-leisure in databases of electronic journals used and that there was no work carried out by the Brazilian researcher. In addition, even if not surpassed the elitization of leisure in museums, being this type of leisure still circumscribed to a population with high level of education and belonging to the middle and upper classes.